Republic of Mozambique : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2016)
This Systematic Country Diagnostic (SCD) is designed to assess the key constraints and opportunities facing Mozambique as it strives to sustain robust growth and macroeconomic stability while accelerating poverty reduction and promoting greater economic inclusiveness. The SCD is organized into six chapters. Chapter two describes the evolution of poverty and inequality, explores their regional and demographic dimensions, and identifies strategies for accelerating poverty reduction. Chapter three analyzes key economic constraints and opportunities, identifying the drivers of recent growth, describing developments in the real sector and assessing emerging challenges associated with the rise of the extractive industries. Chapter four examines the inclusiveness of growth, presenting an in-depth analysis of the labor market, the social sectors and the ongoing urbanization process. Chapter five discusses fiscal, institutional, political, social and environmental risks to the sustainability of growth and poverty reduction. Chapter six completes the analysis by identifying a set of priority objectives for accelerating progress on the World Bank’s twin goals of eliminating extreme poverty and promoting shared prosperity.